Exploring the Influence of Intrinsic Motivation on Entrepreneurial Creativity and Growth in Manufacturing SMEs - Ncube, Thandukwazi Richman (Economics and Entrepreneurship: The Proceedings of the 10\(^{th}\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
Small and medium-sized enterprises (SMEs) play a vital role in driving economic growth, fostering innovation, and generating employment opportunities, especially in emerging economies like South Africa. Recognizing the pivotal role of intrinsic motivational factors in SMEs, success is imperative, as they are increasingly recognized as fundamental determinants of entrepreneurial creativity and growth within this sector. Despite considerable research on intrinsic motivation's impact on creativity and innovation, its specific implications for South African SMEs remain largely unexplored. Drawing upon Self-Determination Theory (SDT), this quantitative study looks into the relationship between intrinsic motivational factors, entrepreneurial creativity, and business growth within the eThekwini District Municipality's Manufacturing SMEs. Through a quantitative study, this research explores the relationship between intrinsic motivational factors, entrepreneurial creativity, and business growth within the eThekwini District Municipality Manufacturing SMEs. A comprehensive questionnaire was administered to 68 SME owners to collect survey data, the research investigates how intrinsic motivation influences creativity and subsequent business growth. The findings underscore the significance of intrinsic motivation in driving creativity, with respondents perceiving it as essential for unlocking creative potential. Moreover, the study highlights the association between self-motivation and heightened creativity, supported by statistical analyses. Notably, SME owners' willingness to take risks is found to be significantly related to business growth, emphasising the strategic importance of intrinsic motivation in fostering entrepreneurial success and advancing national economic goals. By clarifying the mechanisms through which intrinsic motivation drives SME prosperity, this research provides valuable insights for policymakers and stakeholders seeking to support SME development and contribute to South Africa's economic advancement.